Commercial scale production of Yamabushitake mushroom (Hericium erinaceus (Bull.) Pers. 1797) using rubber and bamboo sawdust substrates in tropical regions - Preuk Chutimanukul; Wongsakorn Phatthanamas; Ornprapa Thepsilvisut; Thanin Chantarachot; Akira Thongtip; Panita Chutimanukul (Scientific Reports, 2023)
Abstract Yamabushitake (Hericium erinaceus) is one of the most sought out mushrooms that is widely used for both direct consumption and medicinal purposes. While its demand increases worldwide, cultivation of the mushroom is limited to temperate areas and its production in tropical regions has never been explored. The aim of this study was to test the utilization of rubber and bamboo sawdust, alone or as a substrate mixture, for industrial scale Yamabushitake mushroom production. Five substrate treatments with various ratios of the two sawdust were compared for their physicochemical properties in relation to mushroom productivity. The highest mushroom fresh and dry (113.22 and 23.25 g, respectively), biological efficiency (42.61%), and cap size (9.53 cm) were obtained from the substrates containing 100% rubber sawdust, with the mushroom yield decreasing proportional to the ratio of bamboo sawdust. The 100% rubber sawdust substrate provided a higher initial organic matter and carbon content together with C:N ratio at 63.2%, 36.7% and 65.48, respectively, whereas the 100% bamboo sawdust provided higher nitrogen content (1.03%), which was associated with lower mushroom yield but higher number of fruiting bodies. As in the 100% rubber sawdust substrate, a comparable mushroom yield and growth attributes were also obtained in the 3:1 rubber-bamboo sawdust mixture substrate. Principle component analysis of the measured variables indicated a strong influence of substrate C:N ratio before spawning and the change in substrate electrical conductivity and N content after cultivation to the variation in mushroom productivity among the treatments. The results demonstrate the applicability of rubber sawdust and its combination with up to 25% of bamboo sawdust for Yamabushitake mushroom cultivation and provide the basis for substrate optimization in the tropical Yamabushitake mushroom industry through a circular economy framework.